Preferred temperature of the mexican native cichlid Cichlasoma istlanum (Jordan and Snyder, 1899) - Luna-Figueroa, Jorge; Díaz, Fernando; Espina, Sonia (HIDROBIOLÓGICA, 2017)
Preferred temperature of juvenile Cichlasoma istlanum was 2.1ºC higher (p < 0.05) than that of adults, which had a preferred temperature of 30.5ºC. The thermal preference of juveniles and adults did not differ between day and night. Adults tolerance interval was 33.0% wider than that of the juveniles in reference to higher and lower avoided temperature. The estimated optimum growth temperature for juveniles was 31.6ºC and for adults was 29.5ºC. These results are relevant to optimize the aquacultural practices of C. istlanum in Morelos México; due to the differences in preferred temperature of juveniles and adults it could decreases cannibalism and competition for food between both age groups of the mojarra.